1990
DOI: 10.1152/ajpheart.1990.258.3.h861
|View full text |Cite
|
Sign up to set email alerts
|

Unstimulated force during hypoxia of rat cardiac muscle: stiffness and calcium dependence

Abstract: The stiffness of rat cardiac trabeculae was measured in vitro to distinguish between an increase in unstimulated force (Fu) caused by rapid cycling of cross bridges or caused by rigor bridges during hypoxia. The force was measured with a strain gauge, the sarcomere length was determined by laser diffraction techniques, and muscle length was controlled by means of a motor. Stiffness was analyzed by using small (less than 1% of muscle length) sinusoidal length perturbations of 1 and 100 Hz. The stiffness at 100 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

1991
1991
2006
2006

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 0 publications
0
18
0
Order By: Relevance
“…In this study, we also determined k m by use of sinusoidal muscle length perturbations at frequencies of 1 and 100 Hz. In an active muscle, k m , when measured at 100 Hz of length perturbations, increases as more cross bridges are attached, whereas k m at 1 Hz remains nearly the same compared with a nonactivated muscle (19,36). We have also shown previously that measurement of the k m ratio (100 over 1 Hz) is a sensitive method to establish whether active cross-bridge cycling is present.…”
Section: Force-[ca 2ϩmentioning
confidence: 54%
“…In this study, we also determined k m by use of sinusoidal muscle length perturbations at frequencies of 1 and 100 Hz. In an active muscle, k m , when measured at 100 Hz of length perturbations, increases as more cross bridges are attached, whereas k m at 1 Hz remains nearly the same compared with a nonactivated muscle (19,36). We have also shown previously that measurement of the k m ratio (100 over 1 Hz) is a sensitive method to establish whether active cross-bridge cycling is present.…”
Section: Force-[ca 2ϩmentioning
confidence: 54%
“…To interrogate our data more completely, we utilized the index of cross-bridge cycling (index XB, Eq. 2) devised by Leijendekker et al (25) (Fig. 4).…”
Section: Resultsmentioning
confidence: 96%
“…Because of the well-documented small increase in the amplitude of stiffness with frequency of passive muscle tissue (19,34), index XB will always be Ͼ1. As the name implies, index XB increases with increasing crossbridge activity (25).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…(1) formation of rigor bridges, (2) stimulation of cross bridge cycling and (3) alterations of the elastic properties of the titin filament system. In several ischemia models, it has been shown that the first two conditions, i.e., formation of rigor bridges and stimulation of cross bridge cycling, interact with each other and that both mechanisms contribute to a different degree to resting tension dependent on the degree of ischemia [24].…”
Section: Cardiac Function Of Ab/hspb2-/-micementioning
confidence: 99%